Efficient Group ID-Based Encryption With Equality Test Against Insider Attack. (23rd September 2020) - Ling, Yunhao; Ma, Sha; Huang, Qiong; Li, Ximing; Zhong, Yijian; Ling, Yunzhi
Abstract: ID-based encryption with equality test (IBEET) allows a tester to compare ciphertexts encrypted under different public keys for checking whether they contain the same message. In this paper, we first introduce group mechanism into IBEET and propose a new primitive, namely group ID-based encryption with equality test (G-IBEET). With the group mechanism: (1) group administrator can authorize a tester to make comparison between ciphertexts of group users, but it cannot compare their ciphertexts with any ciphertext of any user who is not in the group. Such group granularity authorization can make IBEET that adapts to group scenario; (2) for the group granularity authorization, only one trapdoor, named group trapdoor, should be issued to the tester, which can greatly reduce the cost of computation, transmission and storage of trapdoors in traditional IBEET schemes; (3) G-IBEET can resist the insider attack launched by the authorized tester, which is an open problem in IBEET. We give definitions for G-IBEET and propose a concrete construction with an efficient test algorithm. We then give its security analysis in the random oracle model.